Estimated Amounts and Rates of Carbon Mobilized by Landsliding in Old‐Growth Temperate Forests of SE Alaska. Issue 11 (19th November 2021) - Vascik, Bryce A.; Booth, Adam M.; Buma, Brian; Berti, Matteo
Abstract: Landslides, a forest disturbance, mobilize carbon (C) sequestered in vegetation and soils. Mobilized C is deposited either onto hillslopes or into the water, sequestering C from and releasing C to the atmosphere at different time scales. The C‐dense old‐growth temperate forests of SE Alaska are a unique location to quantify C mobilization rate by frequent landslides that often evolve into saturated moving masses known as debris flows. In this study, the amount of C mobilized by debris flows over historic time scales was estimated by combining a landslide inventory with maps of modeled biomass and soil carbon. We analyzed SE Alaskan landslides over a 55‐year period where a total of 4.69 ± 0.21 MtC was mobilized, an average rate of 2.5 tC km −2 yr −1 . A single event in August 2015 mobilized 57, 651 ± 3, 266 tC, an average of 63 tC km −2 . Depositional fate was inferred using two methods, a standard stream intersection analysis and a second novel approach using simulated debris flow deposition modeling calibrated to the study area. Approximately 60% of debris flow deposits intersected the stream network (9% into mainstem channels, 91% into small tributaries), consistent with long‐term modeled connectivity, suggesting that debris flows are likely to contribute to globally significant amounts of C buried in local fjord sediments. Our results are consistent with an emerging consensus that landslide disturbances that mobilize organic carbon may play an important role in the global carbon cycle over geologic time, with coastal temperate forests being hotspots of potential carbon sequestration. Plain Language Summary: The amount of carbon stored in forests and soils on Earth plays an important role in the global climate by storing carbon away from the atmosphere. Landslides displace carbon in forests, and there is a need for estimating how much carbon is being relocated in heavily forested areas. Our study estimates the amount of carbon removed from hillslopes by landslides in SE Alaska, one of the most carbon‐rich forests in the United States, and determines where in the landscape this carbon is being transported. Landslides primarily move carbon to either hillslopes or water, which bury carbon and reduce the rate at which it is transferred to the atmosphere. Over a 55‐year period, landslides transported as much as 57% of the amount of carbon that was lost due to logging in the Tongass National Forest between 1954 and 1995. Across the landscape, 60% of the landslides deposit into streams, which increases the chance for carbon to be stored for geologic time scales. These findings agree with previous research showing forest disturbances play an important role in the global carbon cycle that moderates climate over geologic time. Key Points: Landslides mobilized carbon at a rate of 2.46 ± 0.12 tC km −2 yr −1 over 55 years in SE Alaska Relatively high connectivity (60%) of landslide deposition to stream networks facilitates C export to the ocean or fjords Areas with the highest C mobilization rates were areas of moderate landslide frequency in high C density forests